2005
DOI: 10.1089/hum.2005.16.101
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Herpesvirus VP22 Induces Apoptosis in Neuroblastoma Cells by Upregulating the Expression Ratio of Bax to Bcl-2

Abstract: Herpesvirus tegument protein VP22 has been shown to have biotherapeutic potential in tumor gene therapy. Some studies indicate that VP22 may enhance the transfer efficiency of therapeutic proteins by delivering them to more cells while trafficking. Our previous study showed that bovine herpesvirus VP22 (BVP22) enhanced equine herpesvirus thymidine kinase-ganciclovir (Etk-GCV) suicide gene therapy by an unknown intracellular effect. In this study, the interaction between BVP22 and host tumor cells was studied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Then tBid induces oligomerization of BAK and BAX, thereby inducing release of cytochrome c (Wei et al, 2001). Upregulation of Bax/Bcl-2 expression ratio is also a mechanism by which SARS coronavirus and Bovine herpesvirus (VP22 protein) induce mitochondria-mediated apoptosis (Qiu et al, 2005;Ren et al, 2005). Over-expression of Bcl-2 has been shown to inhibit the intrinsic apoptosis pathway mediated by mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Then tBid induces oligomerization of BAK and BAX, thereby inducing release of cytochrome c (Wei et al, 2001). Upregulation of Bax/Bcl-2 expression ratio is also a mechanism by which SARS coronavirus and Bovine herpesvirus (VP22 protein) induce mitochondria-mediated apoptosis (Qiu et al, 2005;Ren et al, 2005). Over-expression of Bcl-2 has been shown to inhibit the intrinsic apoptosis pathway mediated by mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of ORF9p binding to AP-1 via point mutation of ORF9p severely impairs viral growth, most likely by preventing effective viral secondary envelopment ( Lebrun et al, 2018 ). MDV VP22 and HSV-2 VP22 also interact with AP-1 ( Qiu et al, 2005 ). In HSV-1 infected cells, VP22 may be activated via phosphorylation mediated by protein kinases encoded by the CKII and UL13 genes ( Elliott et al, 1996 ; Asai et al, 2007 ).…”
Section: Role Of Vp22 In the Viral Life Cyclementioning
confidence: 99%
“…Apoptosis in the early stage of viral infection prevents replication of the virus, but apoptosis in the late stage of infection is beneficial for the release and spread of progeny virus ( Oral et al, 2016 ; Zhou et al, 2017 ). Transient expression of BoHV-1 VP22 in NXS2 cells does not affect the cell cycle, and analyses of caspase-3 activity and apoptosis have suggested that VP22 induces apoptosis in host tumor cells by upregulating the expression ratio of Bax to Bcl-2 ( Qiu et al, 2005 ). These results suggest that VP22 may promote the spread of viruses by stimulating apoptosis in the late stage of viral infection.…”
Section: Role Of Vp22 In the Viral Life Cyclementioning
confidence: 99%
See 1 more Smart Citation